Pengaruh Kapabilitas Keuangan, Infrastruktur Teknologi, dan Kemampuan Manajerial terhadap Kinerja UKM di Kota Semarang - Sheva Rani Septiya Wibowo; Agus Wibowo (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
Despite the increasing number of SMEs operating in Semarang City, there have been no parallel developments in terms of improving the quality of business performance. A lot of SMEs still find themselves experiencing problems related to their financial capacity, technological adoption, and managerial ability, thus impacting negatively on their operational efficiency and sustainability. Hence, this research attempts to examine the effect of financial capability, technological infrastructure, and managerial capacity on the performance of SMEs in Semarang City. The research was designed quantitatively using the associative approach. Primary data were gathered from 150 SME owners through questionnaires distributed purposively. The data were analyzed using multiple linear regression after being tested for validity, reliability, and classical assumption. Based on the findings, financial capability, technological infrastructure, and managerial capability show a positive and significant impact on the performance of SMEs in Semarang City. However, among the three variables, managerial capability is proven to be the most influential determinant of business performance. This research empirically adds knowledge by combining the three variables into one research design while adding up the Resource-Based View perspective stating that effective internal resources provide a sustainable competitive advantage. The findings highlight the significance of financial literacy, technological acceleration, and managerial training to improve SME's performance. Future research may be done longitudinally and including more variables in the analysis.